Chemostratigraphic and mineralogical examination of the Kilwa Group claystones, coastal Tanzania: An alternative approach to refine the lithostratigraphy. (January 2023) - McCabe, Ross; Nicholas, Christopher J.; Fitches, Bill; Wray, David; Pearce, Tim
Abstract: The Cretaceous and Paleogene marine sedimentary rocks that crop out along southern coastal Tanzania have been the focus of the Tanzanian Drilling Project (TDP) since 2001. The comprehensive lithological and chronostratigraphic examination of over forty shallow cores by the TDP culminated in the formal definition of the Kilwa Group: a claystone-dominated succession comprising five formations deposited in middle to outer shelf and upper slope marine environments along a passive continental margin. Onshore, the TDP has cored important palaeoclimatic events within the Kilwa Group. Offshore, the group forms the reservoir and seal of several gas fields discovered in southern Tanzania. The formations of the Kilwa Group cored onshore, have been differentiated from each other largely by variations in subsidiary lithologies (sandstones and limestones), rather than by diagnostic characteristics of their dominant lithology (olive grey claystone). To test and refine the lithostratigraphy of the Kilwa Group, a forensic examination of the claystones using whole-rock inorganic geochemistry, mineralogical analysis and detailed biostratigraphy, is employed in this study. 1210 core samples collected from 20 onshore TDP boreholes and 185 cutting samples acquired from three wells located in offshore in Blocks 1 and 4 are examined by inductively-coupled plasma optical emission spectroscopy and mass spectrometry, whole-rock and clay fraction X-ray diffraction analysis and heavy mineral analysis using Raman spectroscopy. The different methodologies are used to produce a claystone-based chemostratigraphic framework for the Kilwa Group that comprises three sequences, five packages and six units, and links the shallow subsurface rocks onshore to the deep subsurface stratigraphy offshore. The multidisciplinary geochemical and mineralogical approach reveals that variations in detrital quartz, feldspars (K and Na), heavy minerals, phosphatic minerals and clay minerals (particularly illite, smectite and kaolinite) are key for defining the claystone-based stratigraphy of the Kilwa Group. The variation in the abundance of these mineral through time highlight mostly temporal changes in depositional environment, chemical weathering and sediment provenance that occurred in Tanzania during the Cretaceous and Paleogene. Integration of the chemostratigraphic framework with detailed biostratigraphic information from the study sections and comparison with the published lithostratigraphy of the Kilwa Group onshore reveals that all three stratigraphic schemes are in broad agreement. Nevertheless, refinements are proposed based on the new chemostratigraphic results. It is suggested here that the top and base of the Kilwa Group is older than previously reported (base–Albian and intra-Rupelian, respectively, rather than the end of both stages) and in most cases, the geochemical data suggests that most of the Kilwa Group formations, as cored onshore, are thinner than formerly proposed. Only the Masoko and Lindi Formations are interpreted to be thicker than previously defined by the TDP. Graphical abstract: Image 1 Highlights: The Kilwa Group rocks encountered in the Mandawa and Ruvuma Basins are chemically and mineralogically variable. The compositional variations are caused by changes in sediment provenance, climate and depositional environment. A chemostratigraphic framework is developed for the Kilwa Group claystones that is biostratigraphically constrained. The combined chemostratigraphic and biostratigraphic results have facilitated revisions to the Kilwa Group lithostratigraphy.